(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Malnutrition is the most overlooked form of human deprivation, particularly among preschoolchildren. Millions of Indian children are denied the right to life, health, nutrition, education, and safedrinking water. Interventions for preschool children (Early Childhood Care and Development) in Indiamust cover three areas child health, child developmenteducation, and child nutrition. The study’sspecific objectives are to examine the current nutritional status of preschool children in rural India toanalyse policy priorities related to essential components of early child care and development and itsinterventions and to propose strategies to combat malnutrition among preschool children in India. Avariety of factors influence child nutrition, either directly or indirectly. Three essential components arerequired for preschool children’s strategies in India. They are the food entitlement system, the child caresystem, and the health care system. Malnutrition among preschool children must be addressed as soonas possible. This paper is an attempt in that direction